Las empresas de participación ante el reto de la gestión del cambio demográfico - Martín López, Sonia (REVESCO. Revista de Estudios Cooperativos, 2006)
The demographic change that is lived worldwide, and of particular form in Europe, as consequence of the aging of the population because of the increase of the life expectancy and the drastic reduction of the rates of fertility, has made jump the alarms because of the need to get a suitable management that does not put in danger the financial viability of the social protection systems. The members states have to make the necessary reforms that they lead to the modernization of their social protection systems guaranteeing both suitable and viable pensions and a sanitary assistance and an assistance of long duration of quality, accessible and lasting. To achieve these aims there is a widespread agreement to foment employment policies that stimulate the active aging and the prolongation of the professional life to stop the premature exit of the labour market of the 45-year-old major workers. Among the measurements to adopt for the maintenance of the workers in the companies there are the adjustment of the contents of the working places, the use of the internal knowledge and the permanent training of the workers. In the cases in which already there has been produced the expulsion of the labour market, the participation companies will can represent an exit of the situation of unemployment. But in order that the unemployed ones of major age decide to tackle their own managerial initiative they need formation, advice and helps.
Keywords: Aging population; Systems social protection; Adjustment of the contents of the working places; Workers of major age; Cooperative societies; Employee-owned companies